Malaysian hotel certification in the Islamic tourism industry - Ruzulan, Zulaipa; Jamaludin, Mohammad Aizat; Yahaya, Amiratul Munirah; Fathullah Harun, Hanifah Musa (e-International Publishing House, Ltd., UK, 2022)
Shariah compliant hotel is an essential product in Islamic tourism where many activities could be available there. Thus, certification plays a significant role as a symbol of commitment for the hotel operators to comply with the Shariah principles. By using qualitative methodology, this study aims to explore the Malaysian certification bodies that offer Islamic related certificates to the hotel. There is no standardisation on the certification requirements and approach among the certification bodies to certify the Shariah compliant hotel. Thus, the government should introduce a mechanism to monitor certification to the Shariah compliant hotel.